2019
DOI: 10.3892/ol.2019.10334
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑505 promotes cell proliferation, migration and invasion, and predicts poor prognosis in breast cancer

Abstract: microRNAs are involved in the tumor progression of various cancer types. The present study aimed to determine the prognostic significance of microRNA-505 (miR-505) in patients with breast cancer and investigate the functional role of miR-505 in BCa progression. The expression of miR-505 was estimated using reverse transcription-quantitative polymerase chain reaction. Kaplan-Meier survival curves and Cox regression analysis were used to evaluate the prognostic value of miR-505 in patients with BCa. Cell experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The downregulated expression level of miR-505 has been implicated in breast cancer progression. 33 Also, the restored expression of miR-324-5p significantly mitigated gallbladder carcinoma cell migration, invasion, and epithelial-mesenchymal transit (EMT) in vitro , 14 while the overexpression of miR-361-3p fosters migration and invasion of pancreatic cancer cell in vitro. 10 In our study, the predicted circSERPINE2 target miRNAs, miR-361-3p and miR-324-5p, were found to be remarkably downregulated in GM tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated expression level of miR-505 has been implicated in breast cancer progression. 33 Also, the restored expression of miR-324-5p significantly mitigated gallbladder carcinoma cell migration, invasion, and epithelial-mesenchymal transit (EMT) in vitro , 14 while the overexpression of miR-361-3p fosters migration and invasion of pancreatic cancer cell in vitro. 10 In our study, the predicted circSERPINE2 target miRNAs, miR-361-3p and miR-324-5p, were found to be remarkably downregulated in GM tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hsa-miR-210 and hsa-miR-221 have been linked with BC invasion and poorer prognosis of patients with BC ( Volinia et al, 2012 ). Other miRNAs associated with prognosis in BC include hsa-miR-155, hsa-miR-206, hsa-miR-133b, hsa-miR-10b, let-7b, hsa-miR-30a, and hsa-miR-505 ( Chen et al, 2012 ; Cheng et al, 2012 ; Ma et al, 2014 ; Parrella et al, 2014 ; Quan et al, 2018 ; Wang et al, 2019 ; Yao et al, 2019 ). However, many previous studies have been limited by small numbers of participants or a lack of extensive study scope, which has limited the translation of their findings into clinical application; for instance, the research results of the hsa-miR-30a only apply to triple-negative breast cancer ( Cheng et al, 2012 ), and the study of the hsa-miR-10b has scarce representation in the population of cases classified as low risk by the Nottingham Prognostic Index ( Parrella et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are a kind of small non-coding RNAs that negatively regulate the mRNA translation at the post-transcriptional level. 14,15 Many kinds of research have demonstrated that lncRNAs often target miRNAs directly to exert their role in promoting the progression of cancer. 16 miR-4516 has been proven to regulate the progression of many cancers, including glioblastoma, hepatocellular carcinoma, papillary thyroid carcinomas and so on.…”
Section: Introductionmentioning
confidence: 99%